Analisis Kebijakan Perlindungan Konsumen Dalam Pelayanan Perumda Air Minum Di Kota Soe Kabupaten Timor Tengah Selatan - Hotty, Toni Welem; Mauritsius, Darius; Pello, Helsina F (Law Faculty, Nusa Cendana University, 2025)
This Thesis is entitled “Analysis of the Effectiveness of Consumer Protection Policies in Drinking Water PERUMDA Services in Soe City, South Central Timor Regency” which aims to examine the implementation of consumer protection policies and the obstacles faced by consumer in fulfilling their rights. The research method use is an empirical legal study, with data collection techniques through interviews and questionnaires involving PERUMDA Air Minum employees and costumer. The result showed that the service standards of PERUMDA Air Minum of South Central Timor District in relation to consumer protection policies have been implemented well. However, there are still various challenges, this on known based on 6 indicators of questions given to consumer in the Soe City area showing results that such as water quality that is not up to standard and slow response to consumer complaints and various other technical services. Suqqestions include improving technical services, better socialization to consumers about their rights, and developing a more efficient complaints system. This research is expected to contribute to the improvement of drinking water service quality and consumer protection in the area.